Foundations of public service - Morgan, Douglas F. (Armonk, N.Y. Sharpe, 2008)
Designed to serve as a basic text for an introductory course in Public Administration, this innovative work provides students with an understanding of the basic management functions that are covered in all standard textbooks with two important differences.
Includes bibliographical references (p. 391-411) and index.
Keywords: Public administration --United States